ANALISIS STRUKTURALISME ROBERT STANTON DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Ivi Wiske Panambunan; Syafri Badaruddin; Prasuri Kuswarini (Bajang Institute, 2022)
The purpose of this study is to describe how the characterizations in Tere Liye's novel About You using Robert Stanton's structuralism analysis. The type of this research is descriptive qualitative that uses the structuralism approach of Robert Stanton. The data in this study are in the form of words and sentences. The descriptive method is used to describe the state of the by describing the things that are the centre of attention that support the object of research. The results of the study are 1) the plot used in the novel about Kamuy, which is a back and forth plot, meaning that in the story there is a flashback to the past and future events. Where is the journey of Zaman which traces the pieces of Sri Ningsih's life story from childhood to the end of her life to find the heirs of the treasure she left behind? The storyline of the main character started in 2013 when the Zaman got the task of dealing with the Sri Ningsi wealth case 2013. 2) The setting of this novel About You uses various settings in different times and places. The setting places are Landon, Bungin Island, Surakarta, Jakarta, London, and Paris. 3) The characterization of the main character Sri Ningsih is the main character as a protagonist female and strong character in dealing with problems by showing being smart, great, forgiving, and caring for others.